Pulsed plasma effect in the form of Debye lengths variation on air-suspended carbon nanoparticles - Mahsa Mokhtari; Mohammad Taghi Ahmadi; Amir Musa Abazari; Meisam Rahmani (Environmental Challenges)
The Plasma technique has been regarded as a successful particle pollution control and removal technology with high efficiency and fewer side effects. Carbon-based nanoparticles in exhaust gases caused by cars and industries are notable pollutants that are focused on in this research. Primarily, dielectric barrier discharge (DBD) plasma reactors with two adjustable electrodes are designed. To acquire the optimum plasma effect on nano particles electrodes distance from pollutant source is changed from 2 cm to 32 cm. Obtained histogram images are analyzed which indicate decreased gray points from 62.35 % to 32.26 %. Additionally, an increase in white points from 37.65 % to 76.74 % is reported, which is a sign of absorbed nano-particles by the reactor wall. Additionally, plasma generator factors such as voltages and frequencies are analyzed numerically, revealing the reduction of the polluting nanoparticle concentration by falling off these factors. As the carbon nanoparticles attract pollutants and chemicals like heavy metals and organic contaminants therefore their propagation in the form of Debye length variation under the plasma is investigated.One of the most important pollutants in exhaust gases is carbon nanoparticles, which need to be controlled. Therefore, offering a significant reduction of these particles in exhaust emissions will be in line with the world zero carbon emission program.